The selective isolation and characterization of pathogen bacteria Salmonella sp. from poultry coop soil - Rizka Diah Fitri, .- (Scientific Information & Service Network (ISISnet), 2019)
Poultry commodities in Indonesia had high market prospects. The availability of poultry can decreasedwith the outbreak of disease that attack poultry. This occurrence can cause bacterial infections from the environment such as soil, water and air. This study purposed to detect the presence of Salmonella sp. derived from the poultry coop soil. Pathogenic bacteria was isolated from 3 different sample locations and was selected by using Salmonella Shigella Agar (SSA) selective media. The colonies that successfully isolated were carried out their characteristics. Macroscopic characters of colony were conducted by observing the morphology of bacterial colonies on SSA media, while microscopic characters of cell were carried out with Gram staining. Physicochemical characteristics of soil sample were evaluated by measuring pH, humidity, and soil texture. Based on the result, it was found that pathogenic bacteria from poultry coop soil phenotypically identified as Salmonella sp.